Moving towards more sustainable aquaculture practices: a meta‐analysis on the potential of plant‐enriched diets to improve fish growth, immunity and disease resistance. (28th July 2020) - Reverter, Miriam; Tapissier‐Bontemps, Nathalie; Sarter, Samira; Sasal, Pierre; Caruso, Domenico
Abstract: Aquatic animal diseases are one of the major limiting factors in aquaculture development, with disease emergence forecast to increase with global change. However, in order to treat increasing diseases in a context of global emergence of antimicrobial resistance and strengthening regulations on antimicrobial use, sustainable alternatives are urgently needed. The use of plant supplements to increase fish immunity and disease resistance has gained much popularity within the last decades. The use of functional supplements, such as plants, can also improve growth and feed assimilation, contributing to a better optimization of aquaculture resources (e.g. fish meal inclusion). We conducted a systematic review and meta‐analysis in order to identify the research gaps in the use of plant‐enriched diets in fish aquaculture and estimate, for the first time, the overall efficacy of plant‐enriched diets on fish growth, immunity and disease resistance as well as the effect of intrinsic parameters (fish trophic level, type of plant material, dosage, treatment duration and pathogen species) on the treatment efficacy. We found that plant‐enriched diets significantly enhanced growth, immunity and disease survival of treated fish, regardless of the fish trophic level, treatment duration and type of material used. We also show that plant supplements are a versatile alternative that can benefit different aquaculture sectors (from small‐scale fish farmers to intensive productions). Finally, we observed that studies need to improve the information reported about the plant material used (e.g. origin, identification, chemical composition), in order to allow the comparison of different experiments and improve their repeatability.